Shifting Patterns of Physician Home Visits - Tomoko Sairenji; Anuradha Jetty; Lars E. Peterson (SAGE Publishing, 2016)
Objectives: Home visits have been shown to improve quality of care and lower medical costs for complex elderly patients. We investigated trends in physician home visits and domiciliary care visits as well as physician characteristics associated with providing these services. Design: Longitudinal analysis of Medicare Part B claims data for a national sample of direct patient care physicians in 2006 and 2011. Descriptive statistics were used to characterize the physician sample and to determine numbers of home visits and domiciliary visits in total and by physician specialty. Setting: Patient homes, nursing homes, and domiciliary care facilities. Participants: Direct patient care physicians (n = 22 186). Measurements: Physician demographics, specialty, practice characteristics (practice type, geographic location), number of home visits, and domiciliary visits in 2006 and 2011. Results: We found a small increase (n = 63 501) in total number of home visits made to Medicare beneficiaries between 2006 and 2011 performed by a decreasing percentage of physicians (5.1%, n = 18 165 in 2006; 4.5%, n = 15 296 in 2011). There was substantial growth in domiciliary care visit numbers (n = 218 514) and a small increase in percentage of physicians delivering these services (2.0% in 2006, 2.3% in 2011). Physicians who performed home visits were more likely to be older, in rural locations, specialists in primary care, and more likely to provide nursing home and domiciliary care compared with physicians who did not make any home visits ( P < .05). Conclusion: Home visits and domiciliary visits to Medicare beneficiaries are increasing. General internal medicine physicians provided the highest number of home and domiciliary care visits in 2006, and family physicians did so in 2011. Such delivery models show promise in lowering medical costs while providing high-quality patient care.